Nearly Semiprime Submodules - Salim Al-Mothafar, Nuhad; B.H.Alhakeem, Mohammed (Iraqi Journal of Science, 2023)
Let be a commutative ring with unity and let be a submodule of anon zero left R-module , is called semiprime if whenever , implies . In this paper we say that is nearly semiprime, if whenever , implies ( ),(in short ),where ( )is the Jacobson radical of . We give many results of this type of submodules.